Study Habits and Academic Performance: Basis for the Optimization of Guidance and Counseling Programs - Dimal, Resty John; Salva, Royce (Journal of Interdisciplinary Perspectives, 2025)
Like other student support services, guidance and counseling programs are significant in every educational system. A key aspect of these programs focuses on providing suitable academic support that enhances students’ positive attitudes toward learning. The established significance of this key aspect resulted in the conduct of this quantitative research, initially gauging the study habits and academic performance of 634 pre-university students from various tracks, strands, and levels across private institutions in the Philippines. Through a validated and reliability-tested 50-item questionnaire, the researchers assessed the study habits of the participants. They analyzed the results using parametric (i.e., unpaired t-test) and nonparametric statistical tools (i.e., Kruskal-Wallis H test, Spearman’s rank correlation). The study disclosed that, generally, the participants often take part in their study habits, which created a positive weak correlation with their academic performance. Furthermore, when the results were categorized according to their educational profiles, significant differences emerged in their track-strand and GPA-specific study habits. This suggests that their fields of study and academic standing impact the extent of their study habits, while their grade level does not. In conclusion, the findings emphasize the importance of developing self-awareness among students and optimizing academic support within guidance and counseling programs to address students’ academic demands and contextual needs.